2017
DOI: 10.1002/admi.201700019
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Electrowettable Carbon Nanowall–Diamond Hybrid Materials from Sacrificial Ceramic Templates Using HFCVD

Abstract: Carbon‐on‐carbon materials carry the potential to be a major disruptive technology in fields like energy storage and electronics. In the present work, hot filament chemical vapor deposition (HFCVD) is used to synthesize carbon nanowall (CNW) tetrapods coupled to nanocrystalline diamond in a 3D hybrid network form. The CNW/diamond phase proportion as well as the structural morphology can be easily adjusted by the CVD parameters, allowing a single‐step synthesis of CNW micro‐ and nanopillars or CNW/diamond 3D hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The incorporation of ZnO nanoparticles doped graphene (5 phr) in NR matrix showed significantly improved mechanical properties over that of NR composite filled with conventional-ZnO [ 188 ]. In this context, recently developed carbon based complex hierarchical nanostructures, ZnO tetrapod, 3D interconnected network/hybrids could play a very important role as filler in materials towards development of advanced rubber composites with engineered properties NR and other rubbers [ 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 ].…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…The incorporation of ZnO nanoparticles doped graphene (5 phr) in NR matrix showed significantly improved mechanical properties over that of NR composite filled with conventional-ZnO [ 188 ]. In this context, recently developed carbon based complex hierarchical nanostructures, ZnO tetrapod, 3D interconnected network/hybrids could play a very important role as filler in materials towards development of advanced rubber composites with engineered properties NR and other rubbers [ 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 ].…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…As for using the CVD technique, it is difficult to obtain viable diamond. Nonetheless, the CVD technique makes it possible to provide large-area diamond films on various substrates [4][5][6], and to fabricate diamond films with controlling properties such as free formation, crystal phase, film thickness and doping [7,8]. Therefore, the CVD diamond technique is regarded as an essential technique for the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, newer materials such as Aerographite with micro and nano tubular network structures[ 17 ] have been reported to exhibit very high surface area and large free volume with low density that are flexible and possess outstanding mechanical properties with enormous prospect in supercapacitors to electrocatalyst applications [ 18 , 19 ]. Aerographite decorated by ZnO nanocrystallites have been reported that have promising applications in optoelectronic technologies[ 20 ], aerographite-GaN hybrid networks as possible next generation materials for electronic, photonic and sensors applications[ 21 ], and carbon nanowall (CNW) tetrapods coupled to nanocrystalline diamond in a 3D hybrid form as an excellent candidate for energy storage[ 22 ] are other remarkable examples of advanced 3D carbon-based materials. Also very recently, introduction of ionic groups in the graphene lattice have been reported, exemplifying the first of an ionic graphene salt containing boron[ 23 ].…”
Section: Introductionmentioning
confidence: 99%